2020
DOI: 10.1093/rheumatology/keaa446
|View full text |Cite
|
Sign up to set email alerts
|

Occupational silica exposure in an Australian systemic sclerosis cohort

Abstract: Objective To determine the frequency of self-reported occupational exposure to silica in SSc patients enrolled in the Australian Scleroderma Cohort Study, and to compare the disease characteristics of the silica-exposed patients with those of the non-exposed patients. Method Data collected over a 12-year period from 1670 SSc patients were analysed. We compared the demographic and clinical characteristics of those who reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Considering that SSc may be related to occupation and environmental factors, exposure to dust in these mountainous areas may have affected the prevalence of SSc in our study population. A study in Spain 23 showed that 2.0% of silicosis patients had SSc and a study in Australia 24 showed that 7.5% of SSc patients had occupational dust exposure (which was also more common in men), thus suggesting a relationship of dust exposure with SSc.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that SSc may be related to occupation and environmental factors, exposure to dust in these mountainous areas may have affected the prevalence of SSc in our study population. A study in Spain 23 showed that 2.0% of silicosis patients had SSc and a study in Australia 24 showed that 7.5% of SSc patients had occupational dust exposure (which was also more common in men), thus suggesting a relationship of dust exposure with SSc.…”
Section: Discussionmentioning
confidence: 99%
“…The ASIG registry has contributed to the field of PAH screening 123,124 , GI involvement 125 , overlap syndrome 126 , quality of life 127 , and activity impairment 128 . Furthermore, in the immunological characterization of patients, especially patients with anti-Ku, anti-RNA pol III, and anti-PM75-100 86,[129][130] , also the relation with occupational silica exposure 131 .…”
Section: Australia 2007mentioning
confidence: 99%
“…The SPIN uses a novel research design, the Multiple Cohort Randomized clinical trial Design, to collect longitudinal data related to the problems experienced by people living with SSc and as a framework for the development, evaluation, and delivery of psychosocial and rehabilitation interventions. The first step toward the long-term objectives of the SPIN is the establishment of the SPIN Cohort 131 . It does not have an associated biobank.…”
Section: Scleroderma Patient-centered Intervention Network (Spin) 2012mentioning
confidence: 99%
“…The prevalence of SSc in Canada in 2003 was estimated to be 74.4/100,000 females and 13.3/100,000 males ( 2 ). While SSc is more common in females, the prognosis has been consistently shown to be worse in male patients including more diffuse cutaneous SSc (dcSSc), more interstitial lung disease (ILD) and higher mortality ( 3 , 4 ). It is not known whether this different SSc phenotype and prognosis seen in males is mediated by biological/hormonal influences or whether exposure/occupation related factors in males contribute to the process.…”
Section: Introductionmentioning
confidence: 99%